(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, according to the customs of the German people, where and how funerals are held, whether Germans of the Christian religion belong to the Catholic or Evangelical sect, and funerals differ significantly between the two denominations analyzed in detail.